2018
DOI: 10.5540/03.2018.006.02.0327
|View full text |Cite
|
Sign up to set email alerts
|

Solving Joint Diagonalization Problems via a Riemannian Conjugate Gradient Method in Stiefel Manifold

Abstract: We present a Riemannian Conjugate Gradient (RCG) algorithm to solve the Joint Diagonalization Problem in Stiefel manifolds. We use the special structure of this manifold to build a procedure which avoids extra-calculations associated to vector transportation. Numerical experiments which compare our algorithm with other known procedures are also provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…It can be easily shown that the operator (6) effectively projects matrices from R n×p to the tangent space T X St(n, p). This projection operator was also considered in [27].…”
Section: Preliminariesmentioning
confidence: 99%
“…It can be easily shown that the operator (6) effectively projects matrices from R n×p to the tangent space T X St(n, p). This projection operator was also considered in [27].…”
Section: Preliminariesmentioning
confidence: 99%